Kehalalan Vaksinasi Perspektif Politik Hukum - Muhammad Shohibul Itmam (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
The vaccination program to prevent the spread of COVID-19 and has been declared halal clinically and medically, reinforced by the MUI certificate. However, the vaccination program has not been able to calm the public considering the plurality of legal awareness in Indonesia so that it has drawn controversy that cannot be separated from political elements, interests of the government and stakeholders. This paper that halalness of the vaccination from the perspective of legal politics, approach normative, sociological and phenomenological legal. The findings that the legality of the COVID-19 vaccination is politically influenced by global and humanitarian conditions with the consideration that COVID-19 is a global virus that involves all humanitarian interests, not only Indonesian muslims. So that politically, the law of halal vaccination is a strategic political policy that is appropriate for the current government according to the conditions of Indonesia as a pancasila democracy country, not a religious state and not a secular state but state based on pancasila. The halal vaccination by the government, strengthened by the MUI, is an accommodative political with the national interest, national and religious aspects with spirit of democracy and legal plurality in Indonesia.